Pressure-tuned superconductivity and normal-state behavior in Ba(Fe0.943Co0.057)2As2 near the antiferromagnetic boundary - Liu, W. (2018)
Superconductivity in iron pnictides is unconventional and pairing may be mediated by magnetic fluctuations in the Fe sublattice. Pressure is a clean method to explore superconductivity in iron based superconductors by tuning the ground state continuously without introducing disorder. Here we present a systematic high pressure transport study in Ba(Fe1-xCox)2As2 single crystals with x=0.057, which is near the antiferromagnetic instability. Resistivity ρ=ρ0+ATn was studied under applied pressure up to 7.90 GPa. The parameter n approaches a minimum value of n ≈ 1 at a critical pressure Pc = 3.65 GPa. Near Pc, the superconducting transition temperature Tc reaches a maximum value of 25.8 K. In addition, the superconducting diamagnetism at 2 K shows a sudden change around the same critical pressure. These results may be associated with a possible quantum critical point hidden inside the superconducting dome, near optimum Tc.